Analysis and identification of pollution sources of comprehensive river water quality: Evidence from two river basins in China - Xu, Hanxiao; Gao, Qiang; Yuan, Bin (Ecological indicators, 2022)
•Industry is still the major source of China’s ambient water pollution.•Impact of pollution sources on water quality vary from basin to basin significantly.•Cultivation’s impact on water quality is seasonal.•Cultivation and livestock farming have a cumulative effect on water quality. The identification of the main sources and the impact of the current comprehensive water quality is important in improving the precision and pertinence of water quality management, which will have a significant bearing on the quality of the water environment and the ecological system. This paper focuses on the Yangtze River and Yellow River Basins, employs panel data from 2004–2019 from prefecture-level cities and water quality monitoring sections along the Yangtze and Yellow River main streams, and conducts an empirical study on the effects of pollution sources from cultivation, livestock farming, aquaculture, industry, and domestic activities on the overall water quality. It is found that: (1) Increased pollution from agriculture (cultivation, livestock farming and aquaculture), industry and domestic pollution all contribute to the deterioration of water quality. Industry is still the major source of China’s ambient water pollution. It is then followed by domestic source of pollution and agricultural source of pollution, with the latter having the least impact on water quality. (2) Impact of pollution sources on water quality vary from basin to basin significantly.The main sources of water pollution in the Yangtze and Yellow River Basins are industry and domestic life respectively. Cultivation and aquaculture are the main agricultural sources of water pollution in the two basins respectively. (3) Impact of cultivation pollution sources on water quality is subject to seasonal variations. It means that pollutants from cultivation enter the rivers through the carrying effect of precipitation, and this effect is more often reflected in the busy season. (4) In the long term, the negative impact of cultivation and livestock farming on water quality pollution form a cumulative effect. It grows as the number of lag periods increases. Therefore, in the subsequent environmental pollution control processes, priority should be given to industrial and urban pollution control with more targeted regional pollution management. It is also important to strengthen inter-basin and inter-regional synergistic control, taking top-level design of environmental policies and other conditions of the basin areas into full account to reduce the undesired environmental consequences caused by production.